2021
DOI: 10.5498/wjp.v11.i12.1288
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Dutch version of the displaced aggression questionnaire

Abstract: BACKGROUND Displaced aggression occurs when a person encounters a provoking situation, is unable or unwilling to retaliate against the original provocateur, and subsequently aggresses against a target that is not the source of the initial provocation. The displaced aggression questionnaire (DAQ) was developed to measure individual differences in the tendency to displace aggression. AIM To develop a Dutch version of the DAQ and examine relationships between the DAQ and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Thus, the role of moral disengagement in displaced aggression may be more important than for the usual reactive aggression. This view is partly supported by Smeijers et al (2021), who found that cognitive distortions were related to being selfcentered, blaming others, minimizing/mislabeling, and assuming the worst; that are, the mechanisms of moral disengagement (Zhao & Zhang, 2022) were associated with displaced aggression. Thus, the change in moral disengagement may gradually lead to a corresponding change in displaced aggression.…”
Section: The Mediating Role Of Moral Disengagementmentioning
confidence: 94%
“…Thus, the role of moral disengagement in displaced aggression may be more important than for the usual reactive aggression. This view is partly supported by Smeijers et al (2021), who found that cognitive distortions were related to being selfcentered, blaming others, minimizing/mislabeling, and assuming the worst; that are, the mechanisms of moral disengagement (Zhao & Zhang, 2022) were associated with displaced aggression. Thus, the change in moral disengagement may gradually lead to a corresponding change in displaced aggression.…”
Section: The Mediating Role Of Moral Disengagementmentioning
confidence: 94%
“…Participants indicated that anger expressed by the family is often projected towards the nurses in the form of finding excessive fault with their work. Smeijers et al ( 2021 :122) express displaced anger as aggression towards ‘underserving others’:…”
Section: Theme 1: Emotional Challenges Associated With the Families O...mentioning
confidence: 99%